O impacto da inteligência artificial no ensino de ciências na perspectiva da educação CTS - Corrêa, Bruno de Oliveira (Universidade Federal de São Carlos, 2025)
This work investigates the perceptions of high school students and teachers regarding the use of Artificial Intelligence in science education, seeking to understand how these technologies influence pedagogical practices, learning processes, and socio-technical relationships in the school context. The research starts from the recognition that AI has become part of students' daily lives, while simultaneously raising ethical, pedagogical, and social concerns that demand critical reflection from the perspective of Science, Technology, and Society (STS) education. The central objective was to analyze how different educational actors interpret and give meaning to the presence of AI in the school environment, identifying potential benefits, tensions, and limitations for its responsible integration into the curriculum. The investigation is characterized as a mixed-methods study, articulating quantitative and qualitative procedures. Structured questionnaires were applied to students and teachers, containing perception scales, closed questions, and open-ended questions, in addition to semi-structured interviews with teachers to delve into subjective and contextual dimensions of the phenomenon studied. The data were analyzed using descriptive statistics, content analysis, and interpretive triangulation, allowing for an understanding of the convergences and divergences between the groups. The main results indicate that students demonstrate familiarity and enthusiasm regarding the use of AI, recognizing its potential to facilitate learning, but also revealing ethical concerns, insecurity, and fear of technological dependence. Teachers, on the other hand, showed more cautious perceptions, emphasizing structural limitations, lack of continuing education, and the risks of inappropriate use of AI tools in the school context. The combined analysis shows that the educational use of AI requires critical pedagogical mediation, consistent institutional policies, and training processes that consider the ethical, social, and epistemological dimensions of scientific and technological knowledge. It is concluded that a responsible integration of AI into science education is only possible when articulated with an ECTS (Education, Technology, and Innovation) framework that recognizes technology as a complex sociocultural phenomenon.
The impact of artificial intelligence on science education from a STS Perspective
Keywords: Inteligência artificial; Educação em ciências; Educação CTS; Percepções docentes e discentes; Artificial intelligence; Science education; STS approach; Teachers’ and students’ perceptions; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL; 4. Educação de Qualidade